_ - Clicerio González-Villalpando; Claudio Alberto Dávila-Cervantes; Mireya Zamora-Macorra; Belem Trejo-Valdivia; María Elena González-Villalpando (Salud Pública de México, 2014)
Objective. To describe risk factors associated to the incidence of type 2 diabetes (T2D) in Mexican population and to define phenotypic (clinical, anthropometric, metabolic) characteristics present in the individual who will convert to diabetes, regardless of time of onset. Materials and methods. The Mexico City Diabetes Study began in 1990, with 2 282 participants, and had three subsequent phases: 1994, 1998, and 2008. A systematic evaluation with an oral glucose tolerance test was performed in each phase. For diagnosis of T2D, American Diabetes Association criteria were used. Results. The population at risk was 1939 individuals. Subjects who were in the converter stage (initially non diabetic that eventually converted to T2D) had, at baseline, higher BMI (30 vs 27), systolic blood pressure (119 vs 116 mmHg), fasting glucose (90 vs 82mg/dl), triglycerides (239 vs 196mg/dl), and cholesterol (192 vs 190mg/dl), compared with subjects who remained non converters (p menor que 0.05). Conclusion. The phenotype described represents a potentially identifiable phase and a target for preventive intervention.